Regra-matriz do ICMS e a fenomenologia da redução de base de cálculo - Cunha, Nicodemos Victor Dantas da (2023)
The objective of this thesis is to analyze how ICMS is calculated “from the inside”, in cases where there is a reduction in the calculation base determined by legislation. An analysis is made of the construction of the mathematical formula, capable of introducing the tax amount into its own calculation base, which a priori is identified as being erroneously handled by the interpreters of the system, which are presupposing an automatic and infallible incidence in the tax incidence matrix rule, without using the benefit of reduction of the calculation base. For this reason, a distinction is made between the conceptions of legal incidence to clarify the different reasons used by those who defend this automatic incidence and those who believe that human action is necessary to, interpreting the legislation and integrating the normative commands, apply it. In the end, it is established that the methodology to calculate the tax from the inside, when compared with the commandment of article 13, § 1, I, of the Kandir Law (Complementary Law 87/1996), must be different from the one usually used. Finally, comments are made on the undue extinction of some tax benefits related to the reduction of the calculation base